STUDY OF OXYGEN EVOLUTION REACTION MECHANISM ON NICKEL-COBALT PHOSPHATE CATALYST AS ANODE MATERIAL OF ELECTROLYSIS CELL - Arkan Nuruzzahran, Muhammad
Electrolysis cell is one of the current environmentally friendly tools for producing hydrogen. To produce hydrogen with an electrolysis cell, an electric potential greater than 1.23 V is required. However, it is the oxygen evolution reaction (OER) process at the anode of the electrolysis cell that most influences this potential, so an OER catalyst (anode) that can reduce the electrical potential requirement is needed. To obtain OER catalysts that have this kind of performance, various catalysts have been developed such as transition metal phosphate-based catalysts. One of the transition metal phosphate-based catalysts that has been experimentally reported is nickel-cobalt phosphate catalyst. The experimental results show that nickel-cobalt phosphate catalysts have better performance compared to nickel phosphate catalysts for OER. However, the fundamental mechanism of OER to explain the performance trend of the two OER catalysts is not yet known. In fact, this is important to know in order to develop better transition metal phosphate-based catalysts in the future. Therefore, in this research, a study on the OER mechanism of nickel-cobalt phosphate catalyst as anode of electrolysis cell will be conducted. Computational methods utilising density functional theory will be used to analyse the thermodynamic performance of nickel-cobalt phosphate catalyst in the OER process. The computational simulation results show that in the nickel-cobalt phosphate catalyst, OER will occur at the Co and Ni active sites, and this catalyst has an average overpotential of 0.46V. This shows that the performance of nickel-cobalt phosphate is thermodynamically superior compared to nickel phosphate which only has a computational overpotential value of 0.58 V with Ni active sites. The performance trends of these two catalysts for OER are in agreement with the results reported experimentally.